2018
DOI: 10.1007/s00438-018-1421-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diversity and population structure of three autochthonous Greek sheep breeds assessed with genome-wide DNA arrays

Abstract: In the present study, genome-wide genotyping was applied to characterize the genetic diversity and population structure of three autochthonous Greek breeds: Boutsko, Karagouniko and Chios. Dairy sheep are among the most significant livestock species in Greece numbering approximately 9 million animals which are characterized by large phenotypic variation and reared under various farming systems. A total of 96 animals were genotyped with the Illumina's OvineSNP50K microarray beadchip, to study the population str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 68 publications
1
10
0
4
Order By: Relevance
“…In addition, the observed heterozygosity was consistent with other US sheep including Suffolk, Rambouillet, Columbia, Polypay and Targhee (Zhang et al 2013). However, the breeds in this study had lower observed heterozygosity when compared with Boutsko, Karagouniko and Chios breeds from Greece (Michailidou et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the observed heterozygosity was consistent with other US sheep including Suffolk, Rambouillet, Columbia, Polypay and Targhee (Zhang et al 2013). However, the breeds in this study had lower observed heterozygosity when compared with Boutsko, Karagouniko and Chios breeds from Greece (Michailidou et al 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Especially for Spanish breeds [22], this has been stimulated by seasonal transhumant migrations [23]. Current patterns of genetic diversity have been interpreted in historic and environmental terms, for example in Switzerland [24], mainland Italy [25,26], Sicily [27], Belgium [28], France [19], the Pyrenean region [29], Spain [30], Greece [31], Wales [32], Russia [33], Nepal [34], China [35,36], Iran [37], north Africa [38,39], South Africa [40], Ethiopia [41,42], New-Zealand [43] and the Carribean region [44] and Merino sheep generally [20]. Recurring observations and themes are the contrast between sheep with fat and normal tails [26,33,35,41,42], the influence of Merino sheep [19,20,33,39] or other breeds [25,44], the level of breed separation [27,30,32,38,39,43] and the adaptation to the environment [34,36,…”
Section: Introductionmentioning
confidence: 99%
“…GELASAKIS, G. BANOS, G. ARSENOS sity within and between breeds is an important step towards revealing the genetic architecture of animal traits. Studies aiming to characterize indigenous Greek sheep breeds and assess genetic distances between them have been based on polymorphisms of blood proteins (Rogdakis et al, 1995;Koutsouli and Rogdakis, 2002) and different types of markers such as microsatellite loci (Bizelis et al, 2007;Koutsouli et al, 2007;Ligda et al, 2009;Mastranestasis et al, 2015;Loukovitis et al, 2016), Random Amplified Polymorphic DNA (RAPD) (Mastranestasis et al, 2011) and SNPs (Pariset et al, 2011;Kominakis et al, 2017a;Michailidou et al, 2018). Respective studies on indigenous Greek goats are limited and used either microsatellite markers (Cañon et al, 2006) or SNPs (Pariset et al, 2009).…”
mentioning
confidence: 99%